Tort Liability of Store Manager to Business Invitees of the Corporate Employer - S. Sheldon Weinhaus (Washington University Law Quarterly, 1959)
The purpose of this Article is to consider the basis by which vicarious liability may extend to the manager. As will be indicated, there are two bases for the liability of the corporation: one is as the ultimate master, the other as possessor and occupier of land. Do the same bases apply to the manager?
Keywords: Negligence; Employer and employee; Master & amp; Servant